Does diabetes mellitus affect guided bone regeneration outcomes in individuals undergoing dental implants? A systematic review and meta-analysis - Oliveira, Leandro Machado; Zanatta, Fabricio Batistin; Antoniazzi, Raquel Pippi; Miguez, Patrícia Almeida (Frontiers in Dental Medicine, 2024)
Objectives: This systematic review aimed to verify if diabetes affects vertical and horizontal ridge augmentation in individuals undergoing dental implant treatment with guided bone regeneration (GBR).Methods: Five databases were systematically screened up to September 2023, according to predefined eligibility criteria. The methodological risk of bias of included studies was assessed using the ROBINS-I tool, and GRADE was used to evaluate the certainty of evidence. Random-effects pairwise meta-analyses were used to compare changes in vertical (height) and horizontal (width) alveolar bone dimensions between individuals exposed and unexposed to diabetes, through standardized mean differences (SMDs).Results: Three non-randomized controlled trials met the inclusion criteria, all of which showed a serious risk of bias. The results showed, with overall very low certainty on evidence, that individuals with diabetes did not exhibit a significant difference in horizontal (SMD = -0.41, 95% CI: -0.92 to 0.10) and vertical (SMD = 0.06, 95% CI: -0.43 to 0.56) ridge augmentation compared to the those without diabetes.The available evidence, albeit of very low certainty, suggests that diabetic individuals with moderate or good glycemic control undergoing dental implants and GBR show comparable horizontal and vertical bone gains to their unexposed counterparts.